Mister exam
Examples
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
How to use it?
Equation
:
(Abs(2*log(0.)*5*(x)-3))=-log(0.)*5*(x)
27*9^l
8*(26-x)=5*(26-y)
cosx+1,3-lnx=0
Identical expressions
-y- one , two = four
minus y minus 1,2 equally 4
minus y minus one , two equally four
Similar expressions
y-1,2=4
-y+1,2=4
Solving equations
/
-y-1,2=4
-y-1,2=4 equation
A equation with variable:
+ equation
Solve the equation!
Numerical solution:
Do search numerical solution at
[
,
]
The solution
You have entered
[src]
-y - 6/5 = 4
$$- y - \frac{6}{5} = 4$$
Simplify
Detail solution
Given the linear equation:
-y-(6/5) = 4
Expand brackets in the left part
-y-6/5 = 4
Move free summands (without y)
from left part to right part, we given:
$$- y = \frac{26}{5}$$
Divide both parts of the equation by -1
y = 26/5 / (-1)
We get the answer: y = -26/5
The graph
Plot the graph f1(x)
Plot the graph f2(x)
Rapid solution
[src]
y1 = -26/5
$$y_{1} = - \frac{26}{5}$$
y1 = -26/5
Sum and product of roots
[src]
sum
-26/5
$$- \frac{26}{5}$$
=
-26/5
$$- \frac{26}{5}$$
product
-26/5
$$- \frac{26}{5}$$
=
-26/5
$$- \frac{26}{5}$$
-26/5
Numerical answer
[src]
y1 = -5.2
y1 = -5.2
To see a detailed solution - share to all your student friends
To see a detailed solution,
share to all your student friends: